Taste of Architectural Space: A Study of User Perception (British Journal of Multidisciplinary and Advanced Studies, 2023)
Influence of Architectural characteristics are critical in shaping up the architectural taste of humans. The study examined how user experience and user perception of public buildings in terms of judgement of taste is affected by socio-cultural and economic conditions of the users. The main study included a comprehensive literature review followed by a sequential explanatory design consisting two parts; online questionnaire and Interviews. Results from quantitative analysis using SPSS and qualitative analysis using NVivo confirmed that there are considerable number of correlations between socio economic factors and characteristics. The study discovered strong relationship between financial status of the user and the judgement of architectural taste. At the same time categories like religion and sex have shown moderate relationship. The discovered main factors that affect judgement of architectural taste were function, form, space, proportion, sense of detail and landscaping. Among those; function, space, sense of detail and landscaping were the most concerned factors in designing institutional buildings. The results would be effectively utilized in designing institutional buildings in the future.